Democracy and the «Fourth Estate» - Viktor Petrovich Kirilenko; Georgy Valeryevich Alekseev (Управленческое консультирование)
The special legal status of journalists in democratic society is determined by the efficiency of the communication mechanics in achievement of political goals. Virtual jurisdiction of state is formed under freedom of expression and universal competition. It should be legally secured on the national level and recognized on the level of international law. This jurisdiction is based on the democratic principals: participation and opposition. State institutions which are endowed with specific broadcasting competence in law are politically responsible for the compliance of democratic principals in virtual informational space.